2018
DOI: 10.1016/j.ctrv.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer brain metastases and the immune system: From brain metastases development to treatment

Abstract: Brain metastases (BM) are diagnosed frequently in non-small cell lung cancer (NSCLC) patients. Despite the high incidence of BM (up to 40% in unselected patients), patients with untreated and/or unstable BM were excluded from pivotal immune checkpoint inhibitors (ICI) NSCLC trials. Percentage of patients with stable and treated BM in these trials ranged from 9.1 to 14.7% and ICI benefit over chemotherapy was not always demonstrated. Only small trials have been completed that demonstrated ICI efficacy in locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 91 publications
(170 reference statements)
4
56
0
1
Order By: Relevance
“…Immune checkpoint inhibitors work by activating the immune system against tumor cells, which may explain the potential effect of immunotherapy on CNS metastases [13]. Moreover, NSCLC-derived brain lesions show a higher expression of PD-L1 than the respective primary tumor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors work by activating the immune system against tumor cells, which may explain the potential effect of immunotherapy on CNS metastases [13]. Moreover, NSCLC-derived brain lesions show a higher expression of PD-L1 than the respective primary tumor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the small subgroups of BM patients included in these trials, ICI appears safe [29] . However, outcomes were mixed as some trials demonstrated benefit over chemotherapy and others did not [29] . A rationale for positive response to ICIs includes the inflammatory microenvironment of BM, with the presence of significant tumor-infiltrating lymphocytes (TILs).…”
Section: Srs In Combination With Immunotherapymentioning
confidence: 94%
“…Present data on ICIs for BM from advanced NSCLC is limited. Most ICI clinical trials in NSCLC excluded patients with untreated or unstable BM, yet included stable and treated BM, comprising 6%-17% of included patients [29] . Overall, in the small subgroups of BM patients included in these trials, ICI appears safe [29] .…”
Section: Srs In Combination With Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, guidelines for BM management recommendations are not consensual (reviewed by LEVY et al [4]), and high-level evidence regarding screening and treatment is scarce. Randomised trials specifically including NSCLC BM patients are largely lacking, and patients with untreated and/or unstable, or even all, BM were excluded from most clinical trials (reviewed by EL RASSY et al [5] and MCCOACH et al [6]).…”
Section: Introductionmentioning
confidence: 99%